1967
DOI: 10.1083/jcb.34.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of Mitosis in Amebae

Abstract: The mitotic apparatus (MA) of the giant ameba, Chaos carolinensis, has characteristic sequences of microtubule arrays and deployment of nuclear envelope fragments. If mitotic organisms are subjected to 2C for 5 min, the MA microtubules are completely degraded, and the envelope fragments are released from the chromosomes which remain condensed but lose their metaphase-plate orientation. On warming, microtubules reform but show partial loss of their parallel alignment; displacement of the envelope fragments pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(16 citation statements)
references
References 9 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…Depolymerization of microtubules by low temperature has been recently reported in a variety of cell types, as for instance mitotic apparatus in amebae (Roth, 1967), microtubular system of axopodia in Heliozoa (Tilney et al, 1966;Tilney and Porter, 1967), and mierotubules of the marginal bundle of mammalian blood platelets (Behnke, 1967). In all these examples, warming of the cells yielded microtubule recuperation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depolymerization of microtubules by low temperature has been recently reported in a variety of cell types, as for instance mitotic apparatus in amebae (Roth, 1967), microtubular system of axopodia in Heliozoa (Tilney et al, 1966;Tilney and Porter, 1967), and mierotubules of the marginal bundle of mammalian blood platelets (Behnke, 1967). In all these examples, warming of the cells yielded microtubule recuperation.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the work of Roth (1967), the duration of the cold treatment was 2 hr counted from the moment when the cloacal temperature reached 2°C. Then the animals were demedullated in the cold; their right sciatic nerves were removed and immediately were fixed in cold fixative.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Perhaps microtubules might also be involved, considering (a), reports that in Blastocladiella emersonii they extend upward (as an array of nine sets of three) from the kinetosome region to ensheath the nuclear cap (Lessie & Lovett, 1968;Fuller & Calhoun, 1968), and (b), that low temperatures cause microtubules to disappear in other organisms (Roth, 1967;Tilney & Porter, 1967). At the moment, however, we have no direct evidence to support these possibilities.…”
Section: S S H a W A N D E C C A N T I N Omentioning
confidence: 82%
“…Reproduced from Forer (1965) with kind permission of The Rockefeller University Press. electron microscope (Brinkley & Stubblefield 1966, Harris 1962, Robbins & Gonatas 1964, Roth 1967). In the axopodia of a heliozoan, Tilney et al (1966Tilney et al ( , 1967 demonstrated, by both electron microscopy and polarization optics, the reversible loss of microtubules exposed to cold or hydrostatic pressure and later to colchicine, just as we had seen earlier in the birefringent mitotic spindle filaments in dividing cells.…”
Section: Early Electron Microscopymentioning
confidence: 99%